2020
DOI: 10.1039/d0cy00181c
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable anchoring of Ni/Co cations by oxygen-containing functional groups on functionalized graphite paper and accelerated mass/electron transfer for overall water splitting

Abstract: NCS–NCO/FGP0.44 with a cellular network of porous nanosheets and close-contact heterointerface reveals accelerated interfacial mass/electron transportation for overall water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…For many electrochemical applications that utilize graphitic materials such as batteries, electrolyzers, or supercapacitors, surface-active oxygen functional groups (OFGs) at the electrode are considered essential. [1][2][3] It is widely accepted that OFGs work as an effective catalyst towards the occurring redox reactions in a vanadium flow battery (VFB). [4][5][6][7] This has sparked a lot of scientific as well as industrial activities, which focus on the optimization of the carbon-based electrodes by various oxidative treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many electrochemical applications that utilize graphitic materials such as batteries, electrolyzers, or supercapacitors, surface-active oxygen functional groups (OFGs) at the electrode are considered essential. [1][2][3] It is widely accepted that OFGs work as an effective catalyst towards the occurring redox reactions in a vanadium flow battery (VFB). [4][5][6][7] This has sparked a lot of scientific as well as industrial activities, which focus on the optimization of the carbon-based electrodes by various oxidative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…For many electrochemical applications that utilize graphitic materials such as batteries, electrolyzers, or supercapacitors, surface‐active oxygen functional groups (OFGs) at the electrode are considered essential [1–3] . It is widely accepted that OFGs work as an effective catalyst towards the occurring redox reactions in a vanadium flow battery (VFB) [4–7] .…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al reported that graphite was efficiently activated by CO 2 treatment to change the surface area and surface functional groups, leading to low internal resistance and improved charge collection ability, suggesting the enhanced electrochemical behavior of graphite electrodes [12]. Some previous studies also demonstrated that surface modifications of carbon materials led to an increase in polarity of the surface layer, which facilitated the strong interactions to form the strong covalent interfacial bonding with selected substances for the formation of carbon materials/metal nanocomposites, and further highlight its capability to induce the application of a novel electrochemical-based techniques [13][14][15][16].…”
Section: Introductionmentioning
confidence: 91%
“…These materials have been utilized as supports or metal-free catalysts in many reactions, such as hydrogenation and CO 2 reduction reactions [ 19 , 20 , 21 ]. OCGs on the surface of carbon can synergistically catalyze its reaction with metal components and effectively strengthen its adsorption capability for different reactants, thus sequentially facilitating the high performance of the metal catalyst [ 22 , 23 ]. OCGs in the carbon matrix can induce local charge redistributions, thereby improving the binding affinity between the activators and the carbon atoms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%